EVALUASI TINGKAT EFISIENSI PROGRAM PENDIDIKAN DASAR DI DAERAH ISTIMEWA YOGYAKARTA DENGAN MENGGUNAKAN DATA ENVELOPMENT ANALYSIS - , NURHAZANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the real efforts to achieve transparency and accountability of financial management is the delivery of financial accountability report. in the Government Accounting Standards (Standar Akuntansi Pemerintahan/SAP), mentions the existence of additional information including details on outputs and outcomes in the form of the entity's financial performance indicators, financial report, review programs and other statements regarding the achievement of the entity's financial performance during the reporting period. This study was conducted to fill the dearth of information about the efficiency of basic education programs (compulsory 9 years) and their impact on the quality of primary education outcomes in Yogyakarta. Indicators of educational inputs and outputs were collected from 27 schools in 5 districts/cities in D.I Yogyakarta. To solve the problem specification, analysis DEA is used to measure the efficiency of inputs and outputs. DEA works with schools to identify measures that will be evaluated, then calculated the value of productivity and identify which school does not use inputs efficiently or do not produce output optimally. In general, one of the important findings of this study is the change in policy on curriculum, education financing and policy changes made by the government can affect the outcome of the school. The results of the study are representative of the real conditions at the school level has broad implications for the policy programs of basic education (compulsory 9 years) at the national, provincial, district/city, and education unit itself. Keywords: Efficiency, 9-Year Compulsory Education, DEA